Acid Activation and Bleaching Capacity of Some Clays for Decolourizing Used Oils - K. Aziz, Bakhtyar; A. Abdullah, Muhammad; J. Jubrael, Karim (Asian Journal of Chemistry, 2011)
Different types of clays found in Iraqi Kurdistan region have been characterized and used as bleaching earth for the decolourization of used lubricating oil. Acid treated and untreated usedlubricating oils were bleached by these clays. The clays were acid activated by mineral acids at various temperatures and time period of activations to optimize the best condition for production of good quality bleaching clay. 2M HCl, 1:15 clay/acid ratio, 800 rpm stirring at 70 ºC for 2 h was found to be the optimum conditions. Bleaching experiments were conducted at temperature between 200 and 450 ºC for 3 h. Best decolourization results were obtained from Kiffry region clay after acid activation, which was comparable with standard bleaching earth imported from China and Iran. The results were also compared with Standard Fuller's earth. The adsorption isotherms of the bleaching process were studied and Freundlich equation was more applicable than Langmuir equation for the bleaching process of used lubricating oils by the clay samples. The process is physical adsorption by weak bonds between the dark coloured compounds in oil and the clay adsorbent.